Evolution of water and sediment inflows to the largest reservoir system in Southwest China: Historical patterns and future predictions - Yuning Tan; Wenjie Li; Huaixiang Liu; Hongbo Du; Yu Wan (CATENA, 2026)

Differentiated interfacial regulation by a bio-based polysaccharide depressant for sustainable Cu–Mo flotation separation - Yimin Zhu; Yuning Ma; Hui Li; Wenjie Han; Jie Li; Jie Liu (Minerals Engineering, 2026)

A comprehensive distributed hydrological framework for assessing flood responses to environmental change under multiple human disturbances - Yuhao Wang; Ke Zhang; Edwark Park; Yuning Luo; Jie Liu; Shunzhang Li; Zhaoan Zhang; Yue Kong; Sheng Wang (Journal of Hydrology, 2026)

Silicon-mediated stoichiometric controls on phytoplankton community shifts in the Yangtze and Yellow Rivers - Li Yingxiao; Chi Yuning; Zhong Xiaosong; Liu Xiaotian; Lv Zongqing; Wu Wentao; Ran Xiangbin (Journal of Hydrology, 2026)

Construction of a heterojunction based on polyphthalocyanine and defective ZnIn2S4 for enhanced CO₂ photoreduction performance - Yuxuan Liu; Yuning Liang; Weimeng Chi; Shuohui Li; Yanhua Gao; Ying Chen (Journal of Environmental Chemical Engineering, 2026)

Multi-omics combined with simulated fermentation model for elucidation of variation patterns of lipids and volatiles and its mechanism during black tea fermentation - Linchi Niu; Yuning Feng; Shan Zhang; Zhizhen Fang; Rui Liang; Zhenxing Xu; Xujiang Shan; Qinghua Zhou; Haibo Yuan; Yongwen Jiang; Jia Li (Food Chemistry, 2026)

Profiling flavor quality and chemical signatures of China's representative large-leaf congou black teas by sensory evaluation, metabolite profiling, quantification, and flavor supplementation validation - Shan Zhang; Qianting Zhang; Zijuan Gan; Linchi Niu; Le Chen; Yuning Feng; Qinghua Zhou; Xinchao Wang; Yongwen Jiang; Haibo Yuan; Yuliang Deng; Jia Li (Food Chemistry, 2026)

Heterogeneity analysis of extracellular vesicles from four edible crops: structural characteristics and functional evaluation - Shuhong Li; Kefan Guo; Yuning Song; Shaoting Yuan; Guiyun Chen; Ye Chen (Food Chemistry, 2026)

Mitochondrial pathway-mediated gut cell apoptosis: A key mechanism of nitenpyram toxicity in Diaphorina citri adults - Yuning Li; Huyin Hu; Huanqian Yao; Xinyi Xie; Shuyin He; Cuiting Liu; Veeran Sethuraman; Hanhong Xu; Zhongzhen Wu; Benshui Shu (Journal of Asia-Pacific Entomology, 2026)

Targeting Eustachian Tube Microenvironment: Probiotic Surfactant Utilization for Antimicrobial Peptide Secretion to Prevent Otitis Media - Xichu Duan; Yuning Xing; Wenwen Liu; Li Li (Probiotics and Antimicrobial Proteins, 2026)

Quantitative attribution of seasonal runoff variations in the Yellow River Basin under unsteady conditions using a modified Budyko framework - Junjie Wang; Yuning Chi; Shaoxiong Zhang; Bing Shi; Liting Zhang; Chenjun Du; Xin Li; Baoqi Li; Liqin Yang; Lei Huang; Dian Yuan; Kaiyang Qiu; et al. (Journal of Hydrology, 2026)

Formation mechanisms of a severe springtime ozone episode in the Beibu Gulf, China: The role of the marine “ozone pool” and regional transport - Runxi Pan; Fei Jiang; Shuzhuang Feng; Dewei Yang; Yuning Xie; Hang Li; Yu He; Mengwei Jia; Yanhong Xie; Bei Chen (Atmospheric Pollution Research, 2026)

Integrated hydrogen system analysis across the resource-environment-economy nexus: a case study of China - Maximilian Arras; Anne Yingqiu Liang; Yuning Fu; Zheng Li; Linwei Ma (Journal of Industrial Ecology, 2026)

Coaxial electrospun TiO2@CuO heterojunctions with interfacial charge rearrangement for photothermal oxidation of toluene - Weimin Huang; Ke-Xin Li; Shuzhuo Bai; Shanshan Chen; Fanbin Meng; Bing Qin; Yuning Yang; Zonghui Liu; Wen-Tao Zheng; Zhun Hu (Journal of Environmental Chemical Engineering, 2026)

In situ preparation of heterometallic polyphthalocyanine/ZnIn2S4 heterojunction for efficient photocatalytic CO2 reduction - Yuxuan Liu; Yuning Liang; Weimeng Chi; Shuohui Li; Yanhua Gao; Ying Chen (Environmental Research, 2026)

Reproductive toxicity mechanisms of PNMC: Evidence from mitochondrial dysfunction and hormone synthesis disruption in the KGN cells - Jingyi Xie; Zixuan Pan; Yuhan Du; Kexue Li; Yuning Liu; Qiang Weng; Haolin Zhang (Reproductive Toxicology, 2026)

Development and testing of a scaled floating wind turbine in the wind tunnel for dMATCH framework - Yuning Gao; Xinliang Tian; Yitang Liu; Xin Li; Peng Wang; Binrong Wen; Eddie Yin Kwee Ng (Ocean Engineering, 2026)

Aftermath of marine heatwaves on the growth and physiological performance of Sargassum fusiforme and Sargassum thunbergii - Yaoyao Chu; Fengxiao Hu; Yuning Xue; Yue Wang; Xiongwei Huang; Xiaodong Li; Kang Wang; Xianming Tang; Xinhua Chen (Marine Environmental Research, 2026)

Divergent hydrological responses of multi-depth soil moisture variability to multiple factors on the Loess Plateau, China - Junjie Wang; Shaoxiong Zhang; Yuning Chi; Bing Shi; Xin Li; Baoqi Li; Panxing He (Journal of Hydrology, 2026)

Improving the yield of Monacolin K in solid-state fermentation of Monascus purpureus H164 based on fermentation optimization strategy - Sixu Lin; Xue Yang; Qinghua Yu; Junyao Wang; Bing Li; Yuning Zhang; Xuerui Yan (Fungal Biology, 2026)

Outstanding extrinsic reversible self-healing material for commercial epoxy coating: Dynamic chemistry-based supramolecular interpenetrating polymer networks - Panhua Li; Tingting Luo; Xuanyu Lv; Yuning Shi; Bosen Zhang; Kaixuan Ma; Wanchun Guo; Kesong Tian; Xueai Li; Hui Ying Yang; Haiyan Wang (Chemical Engineering Journal, 2026)

Structural control of nitrogen-doped carbon nanotubes embedded with magnetic nanoparticles enabling tunable electromagnetic response and multifunctional flexible film - Jiantao Sun; Kexin Jin; Jing Wang; Xueai Li; Yue Li; Yuning Shi; Chunsheng Wang; Wanchun Guo; Kesong Tian; Haiyan Wang; Yingdan Liu (Chemical Engineering Journal, 2026)

Highly homogeneous dispersed Ni/Co nanoparticles in carbon controlled by ion coordination to trigger polarization for enhanced microwave absorption - Yuning Shi; Shuang Zhang; Xueai Li; Chunsheng Wang; Hang Li; Jinjin Yang; Kexin Jin; Wanchun Guo; Kesong Tian; Yahui Wang; Haiyan Wang (Chemical Engineering Journal, 2026)

A wholly coherent wireless energy storage and sensing microsystem toward flexible wearable electronics - Qing You; Chang Gao; Mingjian Pan; Tongkun Wei; Weihe Shen; Xuan Yao; Hanyu Wang; Yuning Li; Xue Li; Jingye Sun; Mingqiang Zhu; Tao Deng (Chemical Engineering Journal, 2026)

Biomimetic sequential immuno-osteogenic regulation via a dual-drug delivery system with PDA coating on sulfonated PEEK promotes bone defect repair - Zixuan Wu; Kai Ma; Xiaoyu Guo; Zidong Wu; Zheyue Zhu; Yuning Qu; Weidong Zhu; Chengxin Li; Rui Ma; Pei Yang (Chemical Engineering Journal, 2026)

Molecular Insights into Exoskeletal Remodeling: Transcriptomic Profiling of the Molting Cycle in the Red Swamp Crayfish Procambarus clarkii - Yunkuan Zhu; Yu Xu; Suwan Lu; Yuning Hu; Hui Xu; Jiajia Li; Hai Lin; Xuguang Li; Zhiqiang Xu (Fishes, 2026)
The molting of crustaceans is accompanied by exoskeleton reconstruction. To reveal the molecular regulation mechanism of exoskeleton remodeling, the transcriptomic profiles of the exoskeleton across the entire molting process in the red swamp crayfish Procambarus clarkii were investigated by RNA sequencing, yielding a total of 7671 differentially expressed genes (DEGs) across five different molting stages. Notably, the key DEGs were those related to cuticular exoskeleton synthesis (cuticular proteins), degradation (chitinase 2, chitinase 10) and hardening (chitin deacetylase 1), and their expression abundance varied by 10-fold or greater across the molting cycle. Analysis of Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) showed that significantly enriched pathways included the structural constituents of the cuticle, structural molecule activity, chitin binding of chitin metabolism, and hormone biosynthesis. The expression profiles of nine selected molting-related DEGs were further validated via real-time RT-PCR assays. The acquired unique temporal expression patterns involved in exoskeleton remodeling provide a preliminary insight into the regulation of gene expression during the molting cycle in the red swamp crayfish.

Fracture Propagation of Radial Borehole Fracturing in Conglomerate Reservoirs: A Laboratory Study - Yuning Yong; Shouceng Tian; Zhaoquan Guo; Jianzhuang Li; Jiaheng Zhai; Tianyu Wang (Rock Mechanics and Rock Engineering, 2026)

In vivo CAR-T: a paradigm shift in adoptive cell therapy from bench to beside - Yuanting Cai; Huilei Miao; Yuning Wang; Jiatong Ding; Peiwen Ma; Xiaosong Zhong; Yue Bai; Hengjia Tu; Zhongwei Xu; Guo Zhao; Zhangqiang Xiang; Shuhang Wang; et al. (Science Bulletin, 2026)

Effect of Pulse Injection on Fracture Initiation and Propagation in High-Temperature Granite: Application of Soft Fracturing in Enhanced Geothermal Systems - Xiaoxia Zhou; Tianyu Wang; Jianzhuang Li; Xu Zhang; Yuning Yong; Wenchao Zou; Shouceng Tian; Gensheng Li (Rock Mechanics and Rock Engineering, 2026)

A novel context-aware deep learning framework for ship radiated noise recognition - Di Zeng; Yuning Li; Xianli Pan; Shefeng Yan (Ocean Engineering, 2026)

Photocatalytic-peroxymonosulfate dual activation strategy: Efficient removal of norfloxacin by Z-type heterojunction CoWO4/α-Fe2O3 composite catalyst - Jian Zhang; Xinyan Wang; Zixin Liu; Xin Cheng; Haina Bai; Yuning Zhang; Ruoyi Li (Journal of Environmental Chemical Engineering, 2026)

Behavioral responses of rice field eel (Monopterus albus) under ammonia nitrogen, pH, and nitrite stress based on machine vision - Yifan Zhao; Fei Zhou; Muyan Li; Wenzong Zhou; Weiwei Lv; Weiwei Huang; Hang Yang; Yuning Zhang; Mingyou Li; Zhen Xu; Quan Yuan (Aquaculture, 2026)

Performance evaluation of sustainable development goals (SDGs) for Chinese major coastal cities: A spatially explicit evaluation considering evenness - Chao Liu; Ping Li; Yuning Zhao; Zhiwei Zhang (Ocean & Coastal Management, 2026)

Magneto-thermally driven thermosensitive gel for consistency control: Mechanism and technical key - Zhenyu Yi; Nianyin Li; Yuning He; Yu Tian; Yuanzhao Yao; Sijie Tang; Qingyuan Pu (Fuel, 2026)

Multi-scale quality evaluation and geographical origins discrimination of Ankang green tea by intelligent sensory analysis, selenium elemental analysis and quantitative non-volatile sensometabolomics - Yuning Feng; Linchi Niu; Shan Zhang; Xujiang Shan; Le Chen; Yingbin Zhang; Weidong Dai; Qinghua Zhou; Yongwen Jiang; Haibo Yuan; Jia Li (Food Chemistry, 2026)

Identification of the geographical origin of wild rice field eel (Monopterus albus) in China by stable isotopes - Weiwei Lv; Muyan Li; Yangyang Lu; Yifan Zhao; Weiwei Huang; Hang Yang; Quan Yuan; Yuning Zhang; Mingyou Li; Wei Hu; Chunxia Yao; Danhe Wang; et al. (Food Control, 2026)

Drought-induced shifts in rhizosphere microbiota correlate with reprogramming of floral volatiles in Chrysanthemum morifolium ‘Gongju’ - Zhuannan Chu; Mingzhe Cheng; Yuning Sun; Weiwen Li; Dongmei Yin (Rhizosphere, 2025)

Learning to reason over multi-granularity knowledge graph for zero-shot urban land-use mapping - Yansheng Li; Yu Wang; Lei Yu; Bo Dang; Gang Xu; Zhenyu Zhong; Yuning Wu; Xin Guo; Kang Wu; Zheng Li; Linlin Wang; Jian Wang; et al. (Remote Sensing of Environment, 2025)

GHydroMod-SIM-DAI v1.0: A new distributed hydrological model capable of dynamically recognizing runoff generation mechanisms and accounting for aboveground and underground anthropogenic impacts - Yuhao Wang; Ke Zhang; Yuning Luo; Qinuo Zhang; Zhijia Li; Cheng Yao; Xinyu Chen; Sheng Wang; Jie Liu; Chuntang Zhang; Shunzhang Li (Journal of Hydrology, 2025)

γ-Aminobutyric acid and fat alter soymilk gel properties and functionality via protein remodeling - Kangyong Zhang; Hongwei Tang; Yuning Yang; Zhongjiang Wang; Bailiang Li; Fei Liu (Food Chemistry, 2025)

A flexible bionic bimodal sensor with distinguishing temperature and humidity signals - Xuan Yao; Chang Gao; Mingjian Pan; Tongkun Wei; Weihe Shen; Qing You; Hanyu Wang; Jingru Peng; Danke Chen; Xiaoqiu Tang; Xue Li; Yuning Li; et al. (Chemical Engineering Journal, 2025)

Improvement of methane production from waste activated sludge by ultrasound-activated peracetic acid oxidation - Hui Wang; Xuecheng Li; Yuning Yang; Yufen Wang; Tingting Zhu; Peizhe Sun; Bing-Jie Ni; Yiwen Liu (Chemical Engineering Journal, 2025)

Bifunctional electrolyte inducing uniform Zn deposition and suppressing polyiodide shuttle for long life zinc-iodine batteries with low-temperature applicability - Xiaorong Shi; Lei Dai; Jianjian Zhang; Chang Sun; Zhu Long; Yuning Li (Chemical Engineering Journal, 2025)

Predicting the effects of microplastics on soil properties using machine learning - Xudong Xu; Wenhao Li; Yuning Wang; Xu Zhao; Yu Wang; Lei Wang; Hongwen Sun; Chunguang Liu (Applied Soil Ecology, 2025)

Tire wear particle leachate induces lipid metabolism disorders in Procambarus clarkii, leading to liver inflammation and mitochondrial dysfunction in hepatocytes - Xianghan Liu; Qichen Jiang; Wenzong Zhou; Muyan Li; Chenxi Zhu; Quan Yuan; Yuning Zhang; Hang Yang; Weiwei Huang; Weiwei Lv (Marine Pollution Bulletin, 2025)

Reducing dye pollution: Sustainable reuse of colored cotton waste powders in washing-free flat screen printing - Chengyong Gao; Yuning Liu; Tieling Xing; Xiao Li; Sheng Shi (Sustainable Chemistry and Pharmacy, 2025)

Efficient degradation of norfloxacin by CoWO4/CS/BiOCl-10 Z-type heterojunction photocatalysts based on hydrogen bonding and interfacial interaction - Xinyan Wang; Yuting Zhang; Jian Zhang; Chengpeng Shao; Jiaxing Yang; Yuning Zhang; Ruoyi Li; Zheng Xing (Journal of Environmental Chemical Engineering, 2025)

Bioreduction-assisted synthesis of Co nanoclusters for selective singlet oxygen generation in ciprofloxacin degradation - Yuning Fan; Wenqian Zhang; Yaping Geng; Jiangjun Lin; Yefei Su; Kai Teng; Jiajie wu; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2025)

Study on mechanism of in-situ hydrogen generation based on molecular dynamics simulation from pyrolysis of heavy oil - Houfeng He; Yuning Gong; Mingguo Peng; Haoran Zheng; Tian Feng; Ming Zhang; Qiu Li; Pengcheng Liu (Fuel, 2025)

Lipid profiles and metabolic characteristics of Chinese tea cultivars (Camellia sinensis) with different manufacturing suitabilities by comparative lipidomics using UHPLC-Q-Exactive mass spectrometry - Le Chen; Jianqiang Ma; Linchi Niu; Yuning Feng; Zhizhen Fang; Shan Zhang; Xujiang Shan; Qianting Zhang; Qinghua Zhou; Yongwen Jiang; Haibo Yuan; Jia Li (Food Chemistry, 2025)

Livestock grazing increases soil bacterial alpha-diversity and reduces microbial network complexity in a typical steppe - Yiyang Zhao; Zhaokai Sun; Chengyang Zhou; Yong Ding; Yiran Zhang; Yuning Liu; Li Liu (Agriculture, Ecosystems & Environment, 2025)

Combined transcriptome and metabolome analyses provide insights into host adaptation mechanism of Spodoptera frugiperda to cruciferous vegetables - Benshui Shu; Yuning Li; Cuiting Liu; Junying Wu; Cuiling Ye; Jintian Lin; Jingjing Zhang (Journal of Insect Physiology, 2025)

Quantitative non-volatile sensometabolome of Longjing tea and discrimination of taste quality by sensory analysis, large-scale quantitative metabolomics and machine learning - Xujiang Shan; Linchi Niu; Qianting Zhang; Zhizhen Fang; Yuning Feng; Rui Liang; Zhenxing Xu; Shan Zhang; Le Chen; Weidong Dai; Qinghua Zhou; Yongwen Jiang; et al. (Food Chemistry, 2025)

Initiative invasion promoted photoelectrocatalytic antibacterial function on ZIF-67@CoO@Co foil photoanode - Mengna Ding; Qin Zhang; Fengyan Shi; Liping Zhou; Xinchun Guo; Qiuyue Li; Liulin Luo; Yingchun Miao; Yuning Huo (Chemical Engineering Journal, 2025)

Identification and utilization of a novel large-effect QTL and linked markers for enhancing protein concentration in peanut - Mingjun Wang; Jianbin Guo; Gaorui Jin; Taihua Yang; Weigang Chen; Yuning Chen; Li Huang; Huaiyong Luo; Xiaojing Zhou; Boshou Liao; Huifang Jiang; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

Tissue-specific transcriptome followed by RNAi elucidates the functional roles of phenoloxidase and gustatory receptor in Bactrocera dorsalis to cold and heat stress - Ghulam Murtaza; Farman Ullah; Yuning Wang; Zihua Zhao; Zhihong Li (Journal of Pest Science, 2025)

Revolutionary photoelectrochemical water splitting performance of BiVO₄/Bi₂S₃ heterojunction photoanodes boosted by trace bio-Cr₂O₃ through multiple mechanisms - Yefei Su; Yang Yu; Tingting Xue; Kai Teng; Yuning Fan; Jiangjun Lin; Chang Liu; Qing Qu; Lei Li (Chemical Engineering Journal, 2025)

Regional Wave Spectra Prediction Method Based on Deep Learning - Yuning Liu; Rui Li; Wei Hu; Peng Ren; Chao Xu (Journal of Marine Science and Engineering, 2025)
The wave spectrum, as a key statistical feature describing wave energy distribution, is crucial for understanding wave propagation mechanisms and supporting ocean engineering applications. This study, based on ERA5 reanalysis spectrum data, proposes a model combining CNN and xLSTM for rapid gridded wave spectrum prediction over the Bohai and Yellow Seas domain. It uses 2D gridded spectrum data rather than a spectrum at specific points as input and analyzes the impact of various input factors at different time lags on wave development. The results show that incorporating water depth and mean sea level pressure significantly reduces errors. The model performs well across seasons with the seasonal spatial average root mean square error (SARMSE) of spectral energy remaining below 0.040 m2·s and RMSEs for significant wave height (SWH) and mean wave period (MWP) of 0.138 m and 1.331 s, respectively. At individual points, the spectral density bias is near zero, correlation coefficients range from 0.95 to 0.98, and the peak frequency RMSE is between 0.03 and 0.04 Hz. During a typical cold wave event, the model accurately reproduces the energy evolution and peak frequency shift. Buoy observations confirm that the model effectively tracks significant wave height trends under varying conditions. Moreover, applying a frequency-weighted loss function enhances the model’s ability to capture high-frequency spectral components, further improving prediction accuracy. Overall, the proposed method shows strong performance in spectrum prediction and provides a valuable approach for regional wave spectrum modeling.

Expediting the integration of China into the global rare disease drug development and approval - Jiatong Ding; Huiyao Huang; Yuning Wang; Yiru Hou; Guo Zhao; Yuanting Cai; Shuhang Wang; Xuebo Zhang; Ning Li (Science Bulletin, 2025)

Integration of intelligent sensory evaluation, metabolomics, quantification, and enzyme activity analysis to elucidate the influence of first-drying methods on the flavor formation of congou black tea and its underlying mechanism - Shan Zhang; Qinyan Yu; Linchi Niu; Haibo Yuan; Xujiang Shan; Jinjie Hua; Le Chen; Qianting Zhang; Yuning Feng; Xiaolan Yu; Qinghua Zhou; Yongwen Jiang; et al. (Food Chemistry, 2025)

Preparation of polyvinyl alcohol/pullulan nanofibers and Eudragit® S100/polyvinyl alcohol/pullulan core-shell nanofibers for enhanced probiotic storage and oral viability - Yangrui Wang; Yingxue Yue; Shengjun Yang; Sufang Duan; Yuning Yang; Zhaozhi Wang; Xuetong Li; Bailiang Li; Yupeng Wang (Food Hydrocolloids, 2025)

Corrigendum to “Trace-elements driven up-regulation of secreted proteases expression in the human-pathogenic fungus Trichophyton rubrum” [J. Trace Elem. Med. Biol. 87 (2025) 127580] - Oliver Blechert; Shanyu Lan; Shuzhen Xiong; Yuning Zou; Peicong Li; Jiewei Hu; Jiayuan Li; Ping Zhan (Journal of Trace Elements in Medicine and Biology, 2025)

OH-isoGDGTs as a paleothermometer for bottom seawater temperature in the eastern China marginal seas - Yuning Wang; Huamao Yuan; Jinming Song; Junhui Chen; Fengmin Pan; Qidong Wang; Xuegang Li; Liqin Duan; Ning Li; Yueqi Wang (Chemical Geology, 2025)

Feline gastrointestinal eosinophilic sclerosing fibroplasia in a young ragdoll cat: with surgical management - Jindong Gao; Yuning Li; Yang Xie; Md. F. Rahim; Md. F. Kulyar; Quan Mo; Jianzhong He; Mengdi Zhang; Xing Wu; Jinhua Yin (Veterinary Research Communications, 2025)

Salinity-dependent effects of seawater acidification on growth, photosynthetic physiology and biochemistry of the invasive macroalga Codium fragile - Yaoyao Chu; Yunyun Shi; Yuning Xue; Lianghua He; Xiaodong Li; Xiangzhu Shi; Yinggu Kuang; Xinhua Chen; Chao Zhao (Algal Research, 2025)

Ginsenoside Rb2 Inhibits the Pyroptosis in Myocardial Ischemia Progression Through Regulating the SIRT1 Mediated Deacetylation of ASC - Yuning Li; Wenhua Zhang; Yamin Cai; Dong Yang (Biochemical Genetics, 2025)

Single-cell RNA sequencing reveals the heterogeneity of hepatopancreas cells and their association with gonadal development in the red swamp crayfish Procambarus clarkii - Lin Du; Yuning Hu; Siyu Lu; Xuguang Li; Jiajia Li; Hai Lin; Jiaxin Yang; Yu Xu; Zhiqiang Xu (Aquaculture, 2025)

The influence of γ-aminobutyric acid production and fat content on the gel properties, protein conformation, and nutritional characteristics of fermented milk: Achieved through interactions with milk proteins - Kangyong Zhang; Yang Cheng; Yuning Yang; Yuxing Li; Bailiang Li; Fei Liu (Food Chemistry, 2025)

Investigating the mechanisms of flucarbazone-sodium resistance in Bromus japonicus Thunb - Yuning Lan; Xinhui Xue; Hailan Cui; Ruolin Wang; Ying Sun; Hongjuan Huang; Shouhui Wei; Xiangju Li; Zhaofeng Huang (Plant and Soil, 2025)

Lipidomic profiles of shaking-withering black tea and their metabolic conversion during tea processing - Shan Zhang; Jinjie Hua; Linchi Niu; Haibo Yuan; Le Chen; Xujiang Shan; Qianting Zhang; Yuning Feng; Qinghua Zhou; Yongwen Jiang; Jia Li (Food Chemistry, 2025)

Identification of candidate genes associated with resistance to aflatoxin production in peanut through genetic mapping and transcriptome analysis - Dongxin Huai; Li Huang; Xiaomeng Xue; Bolun Yu; Yingbin Ding; Gaorui Jin; Hao Liu; Manish K. Pandey; Hari Kishan Sudini; Huaiyong Luo; Xiaojing Zhou; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

dMATCH: A novel integrated testing method for floating wind turbine dynamics-concept, framework and delay influence - Yuning Gao; Binrong Wen; Zhihao Jiang; Xin Li; Zhike Peng; Guiyong Zhou; Yirong Xia; Xinliang Tian (Ocean Engineering, 2025)

Evaluating the cumulative impacts of multiple stressors on marine and coastal ecosystems in China's marine waters - Chao Liu; Ping Li; Yuning Zhao; Dahai Liu; Shuo Wang (Environmental Impact Assessment Review, 2025)

Geopolymer armor-reinforced composite membranes for efficient oil–water separation and dye degradation - Chunyan Huang; Zichen Li; Yuning Pan; Zhili Li; Yuanyuan Ge (Chemical Engineering Journal, 2025)

Z-type ZnIn2S4 homojunction for high performance photocatalytic hydrogen evolution - Wenbo Wang; Jie Liu; Mengxia Cui; Xinghua Li; Luyao Niu; Xi Wu; Yuning Chen; Xiaowei Li; Hancheng Zhu; Dan Wang; Changlu Shao (Chemical Engineering Journal, 2025)

Trace-elements driven up-regulation of secreted proteases expression in the human-pathogenic fungus Trichophyton rubrum - Oliver Blechert; Shanyu Lan; Shuzhen Xiong; Yuning Zou; Peicong Li; Jiewei Hu; Jiayuan Li; Ping Zhan (Journal of Trace Elements in Medicine and Biology, 2025)

Collaboratively removal of phosphate and glyphosate from wastewater by a macroscopic Zr-SA/Ce-UIO-66 adsorbent: Performance, mechanisms and applicability - Zhixiang Xu; Dongshan Chen; Xingyu Duan; Yuning Chen; Caiqing Li; Siyuan Li; Yitao Ma; Bin Huang; Xuejun Pan (Journal of Hazardous Materials, 2025)

A comparison increasing the photodegradation power of a Ag/g–C3N4 /CoNi–LDH nanocomposite: Photocatalytic activity toward water treatment - Razieh Fazaeli; Hamid Aliyan; Darrin Richeson; Yuning Li (Journal of Environmental Sciences, 2025)

Anion pillar inserted MOF-74-Cu with customized pore environment for efficient purification of natural gas - Weiqiu Huang; Yankang Zhou; Xufei Li; Xinya Wang; Yuning Li; Fangrui Feng; Xinhan Chai; Jing Zhong (Fuel, 2025)

Dissolved oxygen activated by single-atom-state iron coupled with sodium dithionite for norfloxacin degradation: Efficiency and mechanism - Wei Song; Sen Xu; Caixia Fu; Ruiyi Huang; Hongze Fang; Li Li; Dachao Lin; Yuning Fang; Xing Du; Zhihong Wang (Journal of Cleaner Production, 2025)

Seasonal variation in non-volatile flavor substances of fresh tea leaves (Camellia sinensis) by integrated lipidomics and metabolomics using UHPLC-Q-Exactive mass spectrometry - Le Chen; Shan Zhang; Yuning Feng; Yongwen Jiang; Haibo Yuan; Xujiang Shan; Qianting Zhang; Linchi Niu; Shengnan Wang; Qinghua Zhou; Jia Li (Food Chemistry, 2025)

Assessing thermal comfort for the elderly in historical districts and proposing adaptive urban design strategies: A case study in Zhenjiang, China - Yingnan Li; Yuhan Zhang; Yuedong Wang; Zipeng Song; Zhicheng Zhou; Lu Ding; Cen Chen; Xi Jin; Yuning Cheng (Landscape and Ecological Engineering, 2025)

Milk-derived small extracellular vesicles: a new perspective on dairy nutrition - Yuning Zhang; Yingying Lin; Jian He; Sijia Song; Yujia Luo; Yao Lu; Shuxing Chen; Qingyu Wang; Yixuan Li; Fazheng Ren; Huiyuan Guo (Critical Reviews in Food Science and Nutrition, 2024)

dMATCH: A novel integrated testing method for floating wind turbine dynamics – Potential error and its impact - Yuning Gao; Xinliang Tian; Guangqi Liu; Zhihao Jiang; Da Li; Tao Peng; Guiyong Zhou; Binrong Wen (Ocean Engineering, 2024)

iRainSnowHydro v1.0: A distributed integrated rainfall-runoff and snowmelt-runoff simulation model for alpine watersheds - Yuning Luo; Ke Zhang; Yuhao Wang; Sheng Wang; Nan Wu; Shunzhang Li; Qinuo Zhang; Xinyu Chen; Hongjun Bao (Journal of Hydrology, 2024)

Excellent antibiotic degradation through PMS activation via bio derived Fe-Mn oxides with tunable defect concentration: Synergy between singlet oxygen oxidation and electron transfer - Kai Teng; Jiajie Wu; Yuxi Chen; Lin Ge; Guang Li; Yuning Fan; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2024)

On the Nearshore Significant Wave Height Inversion from Video Images Based on Deep Learning - Chao Xu; Rui Li; Wei Hu; Peng Ren; Yanchen Song; Haoqiang Tian; Zhiyong Wang; Weizhen Xu; Yuning Liu (Journal of Marine Science and Engineering, 2024)
Accurate observation of nearshore waves is crucial for coastal safety. In this study, the feasibility of extracting wave information from wave video images captured by shore-based cameras using deep learning methods was explored, focusing on inverting nearshore significant wave height (SWH) from instantaneous wave video images. The accuracy of deep learning models in classifying wind wave and swell wave images was investigated, providing reliable classification results for SWH inversion research. A classification network named ResNet-SW for wave types with improved ResNet was proposed. On this basis, the impact of instantaneous wave images, meteorological factors, and oceanographic factors on SWH inversion was evaluated, and an inversion network named Inversion-Net for SWH that integrates multiple factors was proposed. The inversion performance was significantly enhanced by the specialized models for wind wave and swell. Additionally, the inversion accuracy and stability were further enhanced by improving the loss function of Inversion-Net. Ultimately, time series inversion results were synthesized from the outputs of multiple models; the final inversion results yielded a mean absolute error of 0.04 m and a mean absolute percentage error of 8.52%. Despite certain limitations, this method can still serve as a useful alternative for wave observation.

Flavonoids of Euphorbia hirta inhibit inflammatory mechanisms via Nrf2 and NF-κB pathways - Xiaolin Bai; Lijun Li; Yuning Wu; Bai Jie (Cell Biochemistry and Biophysics, 2024)

Treatability of odorous dioxanes/dioxolanes in source water: How does molecular flexibility and pre-oxidation affect odorant adsorption - Qi Wang; Yuning Du; Wentao Li; Chunmiao Wang; Junzhi Zhang; Min Yang; Jianwei Yu (Water Research, 2024)

Untargeted metabolomics combined with chemometrics reveals distinct metabolic profiles across two sparkling cider fermentation stages - Wenting Li; Qi Guo; Yuning Zhao; Tianli Yue; Yahong Yuan (Food Research International, 2024)

Magnetic bimetallic nanoparticles confined growth for enhancement of electromagnetic loss in void@Fe@SiO2/Co/C particles - Xueai Li; Kexin Jin; Xiangyan Qu; Yuning Shi; Chunsheng Wang; Wanchun Guo; Kesong Tian; Yahui Wang; Haiyan Wang (Chemical Engineering Journal, 2024)

Enhancing coal seam gas pressure measurement accuracy and preventing leakage through dual chamber pressure balancing in borehole - Zhiming Wang; Yuning Sun; Zhenhua Li; Zhidong Sun; Shuo Zhang; Lipei Ding; Zhenjiang You (Gas Science and Engineering, 2024)

Synergistic photocatalytic-photothermal contribution induced by Pd-TiO2/PEDOT immobilized in PVDF membrane for enhanced water purification - Yacong Yang; Zhihao Cao; Tianhan Shen; Junyang Zhang; Zuofei Gu; Mingwan Zhao; Zongli Xie; Yingchun Miao; Yuning Huo; Hexing Li (Chemical Engineering Journal, 2024)

Regulation of tumorigenesis and ferroptosis in non-small cell lung cancer by a novel BBOX1-AS1/miR-326/PROM2 axis - Jinlu An; Jiang Shi; Chao Yang; Junfang Luo; Yuning Li; Jie Ren; Yuanjun Lv; Yang Zhang (Molecular and Cellular Biochemistry, 2024)

LbCOPT1 is a copper transporter induced in Lycium barbarum mycorrhizal roots, which allows tobacco with improved growth and nutrient uptake - Yuhao Zhou; Yuning Li; Jingru Jia; Yinjun Lu; Beijia Feng; Ming Tang; Haoqiang Zhang (Plant Cell Reports, 2024)

A data-driven approach for predicting depth-averaged velocities in the early stages of underwater glider navigation - Hualing Li; Yaojian Zhou; Yuning Zhao; Meishu Wang; Zijian Wang (Ocean Engineering, 2024)

In situ conversion of ZnO anchored on porous carbon foams to antiflexible ZIF-8-X (X = Co or NH2) for sieving linear and mono-branched hexane isomers - Xufei Li; Yankang Zhou; Weiqiu Huang; Xinya Wang; Yuning Li; Lipei Fu; Jing Zhong; Lin Liu (Chemical Engineering Journal, 2024)

Multi-step Fracturing Radial Boreholes for Efficient Development of Unconventional Gas Reservoirs - Tianyu Wang; Zhaoquan Guo; Zhengchao Ma; Yuning Yong; Gensheng Li; Shouceng Tian (Rock Mechanics and Rock Engineering, 2024)

ENSO-driven hydroclimate changes in central Tibetan Plateau since middle Holocene: Evidence from Zhari Namco’s lake sediments - Changrun Wu; Guangxin Liu; Lu Cong; Xiangzhong Li; Xiangjun Liu; Yuning Liu; Deyan Wu; Yuyan Zhang; Die Bai (Quaternary Science Reviews, 2024)

The Characteristics of Degradation of Enrofloxacin by Vis / BC-BiOI / PMS Photocatalytic System Based on BiOI-Modified Biochar - Yutong Xiang; Bin Tan; Meng Li; Yuning Liu; Xiangyu Liu; Yuwei Ding; Bing Lin; Qian Zhang (Water, Air, & Soil Pollution, 2024)

Developing Prussian blue/wood-derived biochar catalyst for persistent organic pollutant degradation: Preparation, characterization, and mechanism - Dingyuan Zheng; Yuning Wang; Xiaoke Jia; Wenrui Yao; Shuo Wang; Zehuai Li; Ce Sun; Haiyan Tan; Yanhua Zhang (Chemosphere, 2024)

Variations in isoprenoid tetraether lipids through the water column of the Western Pacific Ocean: Implications for sedimentary TEX86 records - Jinqiang Guo; Zongyue Wang; Eric P. Achterberg; Huamao Yuan; Jinming Song; Yuning Wang; Xuegang Li; Liqin Duan; Baoxiao Qu (Geochimica et Cosmochimica Acta, 2024)

Change of soil bacterial communities in chemically stabilized chromium contaminated soils in an accelerated aging experiment - Linying Yao; Yuning He; Peng Zhao; Zhihao Xie; Longfei Jiang; Danni Li; Yueqiao Liu; Rui Ma; Jianli Jia; Dayi Zhang (Journal of Environmental Chemical Engineering, 2024)

Experimental study on crashworthiness and lightweight of cutting-type energy-absorbing structure of magnesium alloy for trains - Tao Li; Yong Peng; Yuning Qiao; Wanying Zhu; Jing Zhang; Kui Wang; Guoquan Xie; Honghao Zhang (Engineering Structures, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Development and experimental validation of a machine learning-based disulfidptosis-related ferroptosis score for hepatocellular carcinoma - Cong Zhang; Tiantian Xu; Kun Ji; Shoujin Cao; Jing Ai; Junhan Pan; Yunbo Cao; Yuning Yang; Li Jing; Jun-Hui Sun (Apoptosis, 2024)

Changes in properties of human milk under different conditions of frozen storage - Kaibo Wang; Yanfeng Zhao; Sijia Song; Yingying Lin; Yujia Luo; Yafei Zhang; Yi Xue; Wusun Li; Yuning Zhang; Yao Lu; Heng Quan; Hao Zhang; et al. (Food Research International, 2024)

Application and development of zero-valent iron (ZVI)-based materials for environmental remediation: A scientometric and visualization analysis - Qiuju Wu; Yijie Sun; Zijing Luo; Xinyan Li; Yi Wen; Yuning Shi; Xuejia Wu; Xinni Huang; Yiyan Zhu; Chao Huang (Environmental Research, 2024)

A maleic anhydride-mediated green and sustainable route for versatile wood platform - Dingyuan Zheng; Zehuai Li; Wenrui Yao; Yuning Wang; Ce Sun; Haiyan Tan; Yanhua Zhang (Chemical Engineering Journal, 2024)

Exergy-economic analysis and multi-objective optimization of a multi-generation system based on efficient waste heat recovery of combined wind turbine and compressed CO2 energy storage system - Yuning Chen; Li Feng; Xuhao Li; Mohammad Zoghi; Kourosh Javaherdeh (Sustainable Cities and Society, 2023)

A method of matching the combustion chamber diameter based on spray characteristics for lateral swirl combustion system - Jiang Chang; Xiangrong Li; Yanlin Chen; Weihua Zhao; Liang Xie; Dong Liu; Yuning Kang (Fuel, 2023)

Experimental studies on the particulate matter emission characteristics of a lateral swirl combustion system for direct injection diesel engines - Dong Liu; Xiangrong Li; Liang Xie; Jiang Chang; Yuning Kang; Zhi Zhang (Environmental Pollution, 2023)

Sequence Stratigraphy, Sedimentology, and Reservoir Characteristics of the Middle Cretaceous Mishrif Formation, South Iraq - Leifu Zhang; Wenqi Zhang; Yong Li; Benbiao Song; Dawang Liu; Ya Deng; Jiacheng Xu; Yuning Wang (Journal of Marine Science and Engineering, 2023)
The Cenomanian–Early Turonian Mishrif Formation is a great contributor to oil production in Iraq. Integrating petrographic, mineralogical, and wireline logging data from 52 wells, this study provides an improved understanding of the sequence stratigraphy, depositional evolution, and reservoir characteristics of the Mishrif Formation in the Mesopotamian Basin, south Iraq. Five types of facies associations are classified: lagoon, shoal, rudist bioherm, shallow marine, and deep marine. Such a classification allows convenient differentiation and interpretation of wireline logs. A sequence stratigraphic framework including five third-order sequences (Mhf 1 to Mhf 5) for the Mishrif Formation is established mainly using wireline logging data of close-distance wells, with the aid of cores and thin sections. Two end-member depositional evolution stages are recognized, from clinoform-like progradational shoal complexes in Mhf 1 within a shallow marine environment, to tidal channels in Mhf 2–3 within a lagoon environment. For Mhf 4–5, abrupt changes in facies associations from north to south indicate the development of an intra-shelf basin where organic-rich mudstones directly overlie the shallow marine grainstone shoals and lagoonal wackestones. Reservoir characteristics and compartmentalization are directly controlled by the sequence stratigraphic framework. Sequence boundaries are featured by wackestones and mudstones overprinted by cementation; they are regionally correlatable and work as regional barriers. Shoal complexes in Mhf 1 and tidal channels in Mhf 2–3 are the main reservoir units. Mudstones and wackestones are intra-reservoir baffles and become more frequently developed towards the south, reflecting the increasing water depth towards south. The characterization of the tidal channels, clinoform-like shoals, and intrashelf basinal deposits in the current study could benefit later development of the Mishrif Formation.

Tracing embodied energy use through global value chains: Channel decomposition and analysis of influential factors - Meng Li; Yuning Gao; Bo Meng; Jing Meng (Ecological Economics, 2023)

Research on the Spatial Differentiation Characteristics and Sustainable Development of UGGp in China - Xia Li; Qingcheng He; Bo Xing; Jin Wu; Yuning Ding; Fang Ren; Yi Ding (Geoheritage, 2023)

Study on Complex Wake Characteristics of Yawed Wind Turbine Using Actuator Line Method - Tengyuan Wang; Shuni Zhou; Chang Cai; Xinbao Wang; Zekun Wang; Yuning Zhang; Kezhong Shi; Xiaohui Zhong; Qingan Li (Journal of Marine Science and Engineering, 2023)
In modern large-scale wind farms, power loss caused by the wake effect is more than 30%, and active yaw control can greatly reduce the influence of the wake effect by deflecting the wind turbine’s wake. The yawed wind turbine’s wake characteristics are complex, and a deep comprehension of a yawed turbine’s wake is necessary. The actuator line method combined with URANS (unsteady Reynold-averaged Navier–Stokes equations) is used to study the yawed wind turbine’s wake characteristics in this paper. Compared with an un-yawed wind turbine, a yawed one has two main characteristics, deflection and deformation. With an increasing yaw angle, turbine wake shows an increasing deflection. The results indicated that deflection at different height was different, the wake profile showed the biggest deflection at about the hub height, while the smallest deflection existed at the top and bottom of the yawed turbine’s wake. This can be visually demonstrated by the evolution of a kidney-shape velocity distribution at the vertical cross-section. Two-dimensional and three-dimensional presentations of velocity deficit distributions are presented in this paper. The evolution of an irregular kidney-shape distribution is discussed in this paper. It is formed by the momentum exchange caused by the counter-rotating vortex pair. The results indicated that the counter-rotating vortex pair was composed of the streamwise vortex flux brought by the tip vortex. Furthermore, when the wind turbine rotated clockwise and yawed clockwise, the negative vorticity of counter-rotating vortex first appeared in the upper left position.

An image-based soil type classification method considering the impact of image acquisition distance factor - Dejiang Wang; Yuning Si; Zhan Shu; Ao Wu; Yajun Wu; Yifan Li (Journal of Soils and Sediments, 2023)

Recovering valuable metals from spent hydrodesulfurization catalysts by co-leaching, dissociation, and stepwise precipitation - Bingxu Chen; Hao Du; Yuning Guo; Shaona Wang; Jianping Peng; Yi Zhang; Lanjie Li; Congmei Xu (Journal of Environmental Chemical Engineering, 2023)

Identification of a stable major sucrose-related QTL and diagnostic marker for flavor improvement in peanut - Weitao Li; Li Huang; Nian Liu; Yuning Chen; Jianbin Guo; Bolun Yu; Huaiyong Luo; Xiaojing Zhou; Dongxin Huai; Weigang Chen; Liying Yan; Xin Wang; et al. (Theoretical and Applied Genetics, 2023)

Material footprints in global value chains with consideration of multinational enterprises - Meng Li; Bo Meng; Yuning Gao; Joaquim J.M. Guilhoto; Keying Wang; Yong Geng (Resources, Conservation and Recycling, 2023)

The Responses of Sediment Bacterial Communities in Chinese Mitten Crab (Eriocheir sinensis) Culture Ponds to Changes in Physicochemical Properties Caused by Sediment Improvement - Tianheng Gao; Nannan Li; Wenlei Xue; Yuning Hu; Hai Lin (Fishes, 2023)
The interaction between nutrients, heavy metals, and sediment bacterial communities play a key role in the health of crabs and the biogeochemical cycles of aquaculture systems. However, the effects of sediment improvement activities in crab culture on nutrients and heavy metals and the response of bacterial communities to the relevant changes are unclear. In this study, 24 water and sediment samples were collected from two aquaculture sites (total of 12 ponds, 6 at each site). High-throughput sequencing was used to determine the structure of the bacterial community and the diversity in water and sediment samples. The relationship between nutrients, heavy metals, and bacterial communities and the changes of the three before and after the improvement of the sediment were analyzed. The results showed that Proteobacteria, Bacteroidetes, Acidobacteria, Chloroflexi, and Firmicutes were predominant at the phylum level of sediment. Sediment improvement has an effect on NH4+-N, sulfide, total organic carbon (TOC), and heavy metals in sediments to varying degrees. In addition, redundancy analysis found that NH4+-N, NO3−-N, TP, and heavy metals were key drivers in crab culture pond sediments. The results of functional prediction showed that carbon, nitrogen, and sulfur metabolism were the dominant processes in the two crab farming areas. Overall, changes in nutrients and heavy metals caused by sediment improvement further affected the structure and function of bacterial communities and may affect biogeochemical cycles. Our study has deepened the understanding of the effects of sediment improvement on nutrients, heavy metals, and bacterial communities in crab culture ponds.

Single and combined toxicity assessment of primary or UV-aged microplastics and adsorbed organic pollutants on microalga Chlorella pyrenoidosa - Wei Song; Caixia Fu; Yuning Fang; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Kalpana Bhatt; Lu Liu; Ningjie Wang; Fang Liu; Shunni Zhu (Environmental Pollution, 2023)

Magnetically-oriented porous hydrogel advances wearable electrochemical solidoid sensing heavy metallic ions - Wanxin Tang; Zhen Gu; Yao Chu; Jian Lv; Li Fan; Xinling liu; Feng Wang; Ye Ying; Jian Zhang; Yuning Jiang; Jiaying Cao; Anni Zhu; et al. (Chemical Engineering Journal, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Stitching electron localized heptazine units with “carbon patches” to regulate exciton dissociation behavior of carbon nitride for photocatalytic elimination of petroleum hydrocarbons - Qi Guo; Yuning Wu; Linhong Xia; Xue-Fang Yu; Kaisheng Zhang; Yujie Du; Lixue Zhang; Hua Tang; Jianbo Cheng; Jianpeng Shang; Yanhua Peng; Zhuo Li; et al. (Chemical Engineering Journal, 2023)

Mannan oligosaccharide (MOS) on growth performance, immunity, inflammatory and antioxidant responses of the common carp (Cyprinus carpio) under ammonia stress - Shuqun Xue; Banghua Xia; Bitao Zhang; Linyuan Li; Yuning Zou; Zhentao Shen; Yifang Xiang; Ying Han; Weixing Chen (Frontiers in Marine Science, 2022)
This study evaluated the potential effects of mannan oligosaccharide (MOS) on the health status of common carp under ammonia stress. The experimental fish were equally divided into four groups. The control group was fed with a basal diet. The ammonia stress group (Am group) was fed with a basal diet and set in the culture environment with 0.15 mg/L NH3. The MOS group was fed 0.2% MOS with a basal diet. The treatment group (MOS/Am group) was fed 0.2% MOS feed under ammonia exposure (NH3, 0.15 mg/L). These groups were fed for 30 d. The results showed that under ammonia stress, the growth performance decreased significantly, and the activities of non-specific immune factors, intestinal digestive enzymes, and antioxidant enzymes decreased significantly. Dietary supplementation of MOS, the growth performance, the activities of non-specific immune factors, intestinal digestive enzymes, and antioxidant enzymes increased. Histopathological studies showed that adding MOS reduced liver, gill, and intestine tissue damage under ammonia exposure. Our study suggests that adding MOS to the diet can improve growth performance, immunity, antioxidant capacity, and intestinal health of the common carp. MOS can effectively alleviate the oxidative damage and inflammatory response caused by ammonia poisoning to common carp.

Investigation of the mechanism of Shen Qi Wan prescription in the treatment of T2DM via network pharmacology and molecular docking - Piaopiao Zhao; Xiaoxiao Zhang; Yuning Gong; Weihua Li; Zengrui Wu; Yun Tang; Guixia Liu (In Silico Pharmacology, 2022)

Effects of azadirachtin on detoxification-related gene expression in the fat bodies of the fall armyworm, Spodoptera frugiperda - Haikuo Yu; Xianmei Yang; Jinghua Dai; Yuning Li; Sethuraman Veeran; Jintian Lin; Benshui Shu (Environmental Science and Pollution Research, 2022)

The Innate Immune Response to Infection by Polyascus gregaria in the Male Chinese Mitten Crab (Eriocheir sinensis), Revealed by Proteomic Analysis - Yanping Yang; Fengjiao Ma; Juanjuan Dong; Lianxing Li; Ping Ren; Yuning Zhang; Yatao Wu; Yinping Wang; Kai Liu; Fang Zhang (Fishes, 2021)
The Chinese mitten crab (Eriocheir sinensis) is a representative catadromous invertebrate of the Yangtze River and a commercial species widely cultivated in China. Both cultivated and wild crabs suffer from a variety of parasites and pathogens, which can result in catastrophic economic losses in aquaculture revenue. Polyascus gregaria, a parasitic barnacle with a highly derived morphology, is specialized in invading these crabs. This study examines the immunological mechanism in E. sinensis infected with P. gregaria. Tandem mass tags (TMT), a specialized method of mass-spectrometry, was used to analyze the infection by P. gregaria resistance at the protein level. In the hepatopancreas of infected crabs, 598 proteins differentially expressed relating to physiological change, of which, 352 were upregulated and 246 were downregulated. Based on this differential protein expression, 104 GO terms and 13 KEGG pathways were significantly enriched. Differentially expressed proteins, such as ATG, cathepsin, serpin, iron-related protein, Rab family, integrin, and lectin, are associated with the lysosome GO term and the autophagy-animal KEGG pathways, both of which likely relate to the immune response to the parasitic P. gregaria infection. These results show the benefit of taking a detailed, protein-level approach to understanding the innate immune response of aquatic invertebrates to macroparasite infection.

Research on a new cationic polyacrylamide (CPAM) with a cationic microblock structure and its enhanced effect on sludge condition and dewatering - Yuning Chen; Xuhao Li; Wang Zizeng; Li Feng; Jiehong Xie; Zeluan Lin; Zhihong Xu; Bingzhi Liu; Xiang Li; Huaili Zheng (Environmental Science and Pollution Research, 2021)

Efficient and high-fidelity base editor with expanded PAM compatibility for cytidine dinucleotide - Zhiquan Liu; Siyu Chen; Yingqi Jia; Huanhuan Shan; Mao Chen; Yuning Song; Liangxue Lai; Zhanjun Li (Science China Life Sciences, 2021)

Serum Iron and Ferritin Levels Are Correlated with Complement C3 - Shuang Wen; Yeqin Sha; Yinling Li; Zhilian Rui; Chenhong Si; Yuning Zhou; Fengfeng Yan; Bicheng Wang; Jingming Hu; Xu Han; Dongyan Shi (Biological Trace Element Research, 2021)

Urine concentrations of perfluoroalkyl acids in children and contributions of dietary factors: a cross-sectional study from Shanghai, China - Juan Li; Jiafan Li; Yuning Ma; Bo Chen; Xirui Wang; Xianting Jiao; Yihui Jin; Zhemin Shen; Tao Yuan; Xiaodan Yu (Environmental Science and Pollution Research, 2021)

A microblock structure type of anionic flocculant for hematite wastewater treatment: template copolymerization mechanism and enhanced flocculation effect - Li Feng; Xuhao Li; Zizeng Wang; Bingzhi Liu; Yuning Chen; Huaili Zheng (Environmental Science and Pollution Research, 2021)

Genetic diversity analysis for narrow-leafed lupin (Lupinus angustifolius L.) by SSR markers - Yishan Ji; Rong Liu; Jinguo Hu; Yuning Huang; Dong Wang; Guan Li; Md. Mosiur Rahman; Hongyan Zhang; Chenyu Wang; Mengwei Li; Tao Yang; Xuxiao Zong (Molecular Biology Reports, 2020)

Discovery of two novel and adjacent QTLs on chromosome B02 controlling resistance against bacterial wilt in peanut variety Zhonghua 6 - Huaiyong Luo; Manish K. Pandey; Ye Zhi; Huan Zhang; Siliang Xu; Jianbin Guo; Bei Wu; Haiwen Chen; Xiaoping Ren; Xiaojing Zhou; Yuning Chen; Weigang Chen; et al. (Theoretical and Applied Genetics, 2020)
Key message Two novel and adjacent genomics and candidate genes for bacterial wilt resistance were identified on chromosome B02 in peanut variety Zhonghua 6 using both traditional QTL mapping and QTL-seq methods. Abstract Peanut ( Arachis hypogaea ) is an important oilseed crop worldwide. Utilization of genetic resistance is the most economic and effective approach to control bacterial wilt, one of the most devastating plant diseases, in peanut production. To accelerate the genetic improvement of bacterial wilt resistance (BWR) in peanut breeding programs, quantitative trait locus (QTL) mapping has been conducted for two resistant varieties. In this context, we deployed linkage mapping as well as sequencing-based mapping approach, QTL-seq, to identify genomic regions and candidate genes for BWR in another highly resistant variety Zhonghua 6. The recombination inbred line population (268 progenies) from the cross Xuhua 13 × Zhonghua 6 was used in BWR evaluation across five environments. QTL mapping using both SSR- and SNP-based genetic maps identified a stable QTL ( qBWRB02-1 ) on chromosome B02 with 37.79–78.86% phenotypic variation explained (PVE) across five environments. The QTL-seq facilitated further dissection of qBWRB02-1 into two adjacent genomic regions, qBWRB02-1-1 (2.81–4.24 Mb) and qBWRB02-1-2 (6.54–8.75 Mb). Mapping of newly developed Kompetitive allele-specific PCR (KASP) markers on the genetic map confirmed their stable expressions across five environments. The effects of qBWRB02-1-1 (49.43–68.86% PVE) were much higher than qBWRB02-1-2 (3.96–6.48% PVE) and other previously reported QTLs. Nineteen putative candidate genes affected by 49 non-synonymous SNPs were identified for qBWRB02-1-1 , and ten of them were predicted to code for disease resistance proteins. The major and stable QTL qBWRB02-1-1 and validated KASP markers could be deployed in genomics-assisted breeding (GAB) to develop improved peanut varieties with enhanced BWR.

MicroRNA-498 inhibits the proliferation, migration and invasion of gastric cancer through targeting BMI-1 and suppressing AKT pathway - Dong You; Dawei Wang; Peiji Liu; Yuning Chu; Xueying Zhang; Xueli Ding; Xiaoyu Li; Tao Mao; Xue Jing; Zibin Tian; Yinghua Pan (Human Cell, 2020)

High-resolution mapping of a major and consensus quantitative trait locus for oil content to a ~ 0.8-Mb region on chromosome A08 in peanut (Arachis hypogaea L.) - Nian Liu; Jianbin Guo; Xiaojing Zhou; Bei Wu; Li Huang; Huaiyong Luo; Yuning Chen; Weigang Chen; Yong Lei; Yi Huang; Boshou Liao; Huifang Jiang (Theoretical and Applied Genetics, 2020)
Key message ddRAD-seq-based high-density genetic map comprising 2595 loci identified a major and consensus QTL with a linked marker in a 0.8-Mb physical interval for oil content in peanut. Abstract Enhancing oil content is an important breeding objective in peanut. High-resolution mapping of quantitative trait loci (QTLs) with linked markers could facilitate marker-assisted selection in breeding for target traits. In the present study, a recombined inbred line population (Xuhua 13 × Zhonghua 6) was used to construct a genetic map based on double-digest restriction-site-associated DNA sequencing (ddRAD-seq). The resulting high-density genetic map contained 2595 loci, and spanned a length of 2465.62 cM, with an average distance of 0.95 cM/locus. Seven QTLs for oil content were identified on five linkage groups, including the major and stable QTL qOCA08.1 on chromosome A08 with 10.14–27.19% phenotypic variation explained. The physical interval of qOCA08.1 was further delimited to a ~ 0.8-Mb genomic region where two genes affecting oil synthesis had been annotated. The marker SNPOCA08 was developed targeting the SNP loci associated with oil content and validated in peanut cultivars with diverse oil contents. The major and stable QTL identified in the present study could be further dissected for gene discovery. Furthermore, the tightly linked marker for oil content would be useful in marker-assisted breeding in peanut.

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Chromosomes A07 and A05 associated with stable and major QTLs for pod weight and size in cultivated peanut (Arachis hypogaea L.) - Huaiyong Luo; Jianbin Guo; Xiaoping Ren; Weigang Chen; Li Huang; Xiaojing Zhou; Yuning Chen; Nian Liu; Fei Xiong; Yong Lei; Boshou Liao; Huifang Jiang (Theoretical and Applied Genetics, 2018)

Development of SSR markers and identification of major quantitative trait loci controlling shelling percentage in cultivated peanut (Arachis hypogaea L.) - Huaiyong Luo; Zhijun Xu; Zhendong Li; Xinping Li; Jianwei Lv; Xiaoping Ren; Li Huang; Xiaojing Zhou; Yuning Chen; Jingyin Yu; Weigang Chen; Yong Lei; et al. (Theoretical and Applied Genetics, 2017)

Chemical composition, antioxidant and cytoprotective activities of lotus receptacle - Weicheng Hu; Gongcheng Wang; Ting Shen; Yuning Wang; Boran Hu; Xinfeng Wang; Lei Wu; Pengxia Li; Lilian Ji (Horticulture, Environment, and Biotechnology, 2015)

Quantitative trait locus analysis of agronomic and quality-related traits in cultivated peanut (Arachis hypogaea L.) - Li Huang; Haiyan He; Weigang Chen; Xiaoping Ren; Yuning Chen; Xiaojing Zhou; Youlin Xia; Xiaolin Wang; Xiangguo Jiang; Boshou Liao; Huifang Jiang (Theoretical and Applied Genetics, 2015)

Genomic imprinting analysis of Igf2/H19 in porcine cloned fetuses using parthenogenetic somatic cells as nuclear donors - Dongxu Wang; Yuning Song; Yongye Huang; Feifei Duan; Qinyan Lv; Hongsheng Ouyang; Liangxue Lai; Zhanjun Li (Biotechnology Letters, 2014)

Control of postharvest soft rot caused by Erwinia carotovora of vegetables by a strain of Bacillus amyloliquefaciens and its potential modes of action - Yancun Zhao; Pengxia Li; Kaihong Huang; Yuning Wang; Huali Hu; Ya Sun (World Journal of Microbiology and Biotechnology, 2013)

Antigenic and genetic characterization of a European avian-like H1N1 swine influenza virus from a boy in China in 2011 - Xian Qi; Lunbiao Cui; Yongjun Jiao; Yuning Pan; Xihan Li; Rongqiang Zu; Xiang Huo; Bin Wu; Fengyang Tang; Yongchun Song; Minghao Zhou; Hua Wang; et al. (Archives of Virology, 2013)